Associations of potentially inappropriate medication use with four year survival of an inception cohort of nursing home residents. (January 2019) - Paque, Kristel; Elseviers, Monique; Vander Stichele, Robert; Dilles, Tinne; Pardon, Koen; Deliens, Luc; Christiaens, Thierry
Highlights: 36% of nursing home residents were still alive after 4 years. Polypharmacy and PIM use were high. People with dementia and high care dependency died earlier. No association between polypharmacy or PIM use and survival. Abstract: Background: Survival in older adults has a high variability. The possible association of length of survival with potentially inappropriate medication (PIM) use remains unclear. Aim: To examine the four-year survival rate, the prevalence of polypharmacy and PIM use at admission, and the association between the two, in an inception cohort of newly admitted nursing home residents Methods: Data were used from ageing@NH, a prospective observational cohort study in nursing homes. Residents (n = 613) were followed for four years after admission or until death. PIM use was measured at admission, using STOPPFrail. The Kaplan-Meier method was used to estimate survival, using log-rank tests for subgroup analyses. Cox regression analyses was used to explore associations with PIM use and polypharmacy, corrected for covariates Results: Mean age was 84, 65% were females. After one, two, three and four years the survival rates were respectively 79%, 60.5%, 47% and 36%. At admission, 47% had polypharmacy and 40% excessive polypharmacy, 11% did not use any PIMs, and respectively 28%, 29%, and 32% used one, two and three or more PIMs. No difference in survival was found between polypharmacy and no polypharmacy, and PIM use and no PIM use at admission. Neither polypharmacy nor PIM use at admission were associated with mortality. Conclusion: Residents survived a relatively short time after NH admission. Polypharmacy and PIM use at admission were relatively high in this cohort, although neither was associated with mortality.